IDENTIFICATION AND RESEARCH OF THE PROPERTIES OF LACTIC ACID BACTERIA STRAINS USED AS STARTER CULTURES FOR MAKING RAW-SMOKED HORSEMEAT SAUSAGES - М. Iliyaskyzy; U.Ch. Chomanov; Z. Zh. Seidakhmetova (Academic Journal of Physical and Chemical Sciences, 2019)
This article is about identification of flora of raw smoked sausages produced in the course of study, which will enable a further study of its properties and use in the production of raw smoked sausage from horse meat. The article describes the current state of the world market for horse meat and meat products; and production of sausages, including raw smoked sausages. There is a technology that has been developed in order to produce horse meat products using starter cultures: ready cooked smoked Kazy and raw smoked sausage. The hip portion, which remains after jaya is cut off, is used as the main stock for the production of raw smoked sausage. We compared the quality characteristics of the finished products, and studied the amino acid and fatty acid composition. We provided a comparative description for the organoleptic parameters of raw smoked sausages with starter cultures and a reference sample added. The samples were compared for: pH value, content of mass fraction of protein and microbiological characteristics. We tested elective nutrient medium for lactic acid bacteria in order to see if there was any significant microbial flora in raw smoked sausages.